Mothers and Babies Online Course: Participant Characteristics and Behaviors in a Web-Based Prevention of Postpartum Depression Intervention - Barrera, Alinne Z.; Morris, Sydney Y.; Ruiz, Adriana (Frontiers in Global Women's Health, 2022)
Despite the availability of evidence-based postpartum depression (PPD) prevention and treatment interventions, perinatal persons continue to suffer. eHealth and mHealth tools to address mental health issues have grown exponentially, especially given the ubiquity of technology and the increased demand for telemental health resources. The Mothers and Babies Online Course (eMB), an 8-lesson prevention of PPD intervention, was digitally adapted to expand the reach of evidence-based interventions to perinatal persons with limited access to maternal mental health resources. This report describes the characteristics, behaviors, and feedback provided by users of the updated eMB website. Two hundred eight predominantly English-speaking U.S. residents enrolled in the eMB. Thirty-seven percent were either pregnant (n=38) or postpartum (n=39) women interested in learning skills to manage changes in their mood during and after pregnancy; 63% were health providers (n=131) interested in learning how to support their patient communities. Seventy-six percent (n=159) viewed at least one of the eight eMB lessons, with 50.9% exclusively viewing Lesson 1. Few (4.4%) viewed all eight lessons. The lessons were rated favorably on usefulness and understanding. Perinatal women engaged with interactive content at higher rates than health providers. Examining user behaviors and feedback is an essential developmental step before empirically testing digital tools' effectiveness. Future iterations of the eMB will incorporate these preliminary findings to provide perinatal persons with accessible web-based interventions that will hopefully reduce the incidence and negative consequences of postpartum depression.